2012
DOI: 10.1101/gad.191973.112
|View full text |Cite
|
Sign up to set email alerts
|

The p110α and p110β isoforms of PI3K play divergent roles in mammary gland development and tumorigenesis

Abstract: Class Ia phosphatidylinositol 3 kinase (PI3K) is required for oncogenic receptor-mediated transformation; however, the individual roles of the two commonly expressed class Ia PI3K isoforms in oncogenic receptor signaling have not been elucidated in vivo. Here, we show that genetic ablation of p110a blocks tumor formation in both polyoma middle T antigen (MT) and HER2/Neu transgenic models of breast cancer. Surprisingly, p110b ablation results in both increased ductal branching and tumorigenesis. Biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 45 publications
12
115
0
2
Order By: Relevance
“…Despite this, the R-Ras2-dependent PI3Ka pool is clearly relevant in vivo, given the marked tumorigenic and metastatic defects shown by R-Ras2-deficient breast cancer cells when implanted in recipient mice. The morphogenetic alterations seen in preneoplasic mammary glands of MMTV-Her2 tg ;Rras2 À / À mice, together with the signalling compensation events detected in tumours arising in those mice, are also indirect evidence in favour of defects in the PI3Ka/Akt/ mTORC route in this experimental model 30,31,[39][40][41][42][43][44][45] . However, as reconstitution experiments are not possible in this case, we cannot formally exclude the possibility that those events could be generated by defects in other R-Ras2-dependent signalling routes (Supplementary Discussion).…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 65%
See 1 more Smart Citation
“…Despite this, the R-Ras2-dependent PI3Ka pool is clearly relevant in vivo, given the marked tumorigenic and metastatic defects shown by R-Ras2-deficient breast cancer cells when implanted in recipient mice. The morphogenetic alterations seen in preneoplasic mammary glands of MMTV-Her2 tg ;Rras2 À / À mice, together with the signalling compensation events detected in tumours arising in those mice, are also indirect evidence in favour of defects in the PI3Ka/Akt/ mTORC route in this experimental model 30,31,[39][40][41][42][43][44][45] . However, as reconstitution experiments are not possible in this case, we cannot formally exclude the possibility that those events could be generated by defects in other R-Ras2-dependent signalling routes (Supplementary Discussion).…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 65%
“…In this transgenic system, the overexpression of the wild-type Her2 receptor (also known as Neu and Erbb2) in breast epithelial cells triggers mammary gland hyperplasia and, eventually, breast cancer. Thus, it recapitulates the transforming events that take place in human Her2 þ breast tumours, a frequent PI3Ka/Akt-dependent breast cancer subtype 30,31 . To investigate the participation of R-Ras2 in this stepwise tumorigenic programme, we first analysed the structure of pre-neoplasic mammary glands in cohorts of pubertal MMTVHer2 tg ;Rras2 þ / þ and MMTV-Her2 tg ;Rras2 À / À female mice.…”
Section: R-ras2 Uses Different Downstream Effectors During Metastasismentioning
confidence: 72%
“…Thus, there is considerable need to determine the isoform dependence of a given tumor class. Recent work in model systems and human tumor cell lines has shown that tumors driven by oncogenes and activated receptors such as HER2 depend on p110α, suggesting that inhibitors targeting this isoform might be efficacious in this tumor class (16). Our original work and that of others has shown that many PTEN-null tumors depend on p110β (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 85%
“…It is conceivable that the signal intensity of the p110β-dependent input is much lower than the Kras-generated signal carried by p110α. This possibility, together with the fact that p110α has a stronger kinase activity than p110β (16,39), would explain the shift toward a p110α requirement. Alternatively, it is possible that activation of Kras both activates p110α and shuts off the signal responsible for p110β activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation